Distal Ruthenaelectro‐Catalyzed meta‐C−H Bromination with Aqueous HBr. Issue 20 (16th March 2022) - Wang, Yulei; Simon, Hendrik; Chen, Xinran; Lin, Zhipeng; Chen, Shan; Ackermann, Lutz
Abstract: While electrochemical ortho ‐selective C−H activations are well established, distal C−H activations continue to be underdeveloped. In contrast, we herein describe the electrochemical meta ‐C−H functionalization. The remote C−H bromination was accomplished in an undivided cell by RuCl3 ⋅3 H2 O with aqueous HBr. The electrohalogenation proceeded under exogenous ligand‐ and electrolyte‐free conditions. Notably, pyrazolylarenes were meta ‐selectively brominated at the benzenoid moiety, rather than on the electron‐rich pyrazole ring for the first time. Mechanistic studies were suggestive of an initial ruthenacycle formation, and a subsequent ligand‐to‐ligand hydrogen transfer (LLHT) process to liberate the brominated product. Abstract : The first electrochemical transition‐metal‐catalyzed meta ‐C−H functionalization has been accomplished, affording the positionally selective bromination product in an undivided cell by the catalysis of readily available RuCl3 ⋅3 H2 O with aqueous HBr as the brominating agent.